Targeted metabolomics in the expanded newborn screening for inborn errors of metabolism1. Issue 6 (19th June 2015) - Scolamiero, Emanuela; Cozzolino, Carla; Albano, Lucia; Ansalone, Antonella; Caterino, Marianna; Corbo, Graziella; di Girolamo, Maria Grazia; Di Stefano, Cristina; Durante, Adriano; Franzese, Giovanni; Franzese, Ignazio; Gallo, Giovanna; et al.
<x xml:space="preserve">Abstract</x> This paper highlights the importance of metabolic profiling by LC-MS/MS and GC-MS of biological fluids for diagnosis of inborn errors of metabolism and confirms a high incidence of these disorders.